Diet Influences Expression of Autoimmune‐Associated Genes and Disease Severity by Epigenetic Mechanisms in a Transgenic Mouse Model of Lupus. Issue 7 (2nd July 2013) - Strickland, Faith M.; Hewagama, Anura; Wu, Ailing; Sawalha, Amr H.; Delaney, Colin; Hoeltzel, Mark F.; Yung, Raymond; Johnson, Kent; Mickelson, Barbara; Richardson, Bruce C.
Abstract : Objective: Lupus flares occur when genetically predisposed individuals encounter appropriate environmental agents. Current evidence indicates that the environment contributes by inhibiting T cell DNA methylation, causing overexpression of normally silenced genes. DNA methylation depends on both dietary transmethylation micronutrients and ERK‐regulated DNA methyltransferase 1 (DNMT‐1) levels. We used transgenic mice to study the effect of interactions between diet, DNMT‐1 levels, and genetic predisposition on the development and severity of lupus. Methods: A doxycycline‐inducible ERK defect was bred into lupus‐resistant (C57BL/6) and lupus‐susceptible (C57BL/6 × SJL) mouse strains. Doxycycline‐treated mice were fed a standard commercial diet for 18 weeks and then switched to a transmethylation micronutrient–supplemented (MS) or –restricted (MR) diet. Disease severity was assessed by examining anti–double‐stranded DNA (anti‐dsDNA) antibody levels, the presence of proteinuria and hematuria, and by histopathologic analysis of kidney tissues. Pyrosequencing was used to determine micronutrient effects on DNA methylation. Results: Doxycycline induced modest levels of anti‐dsDNA antibodies in C57BL/6 mice and higher levels in C57BL/6 × SJL mice. Doxycycline‐treated C57BL/6 × SJL mice developed hematuria and glomerulonephritis on the MR and standard diets but not the MS diet. In contrast, C57BL/6 mice developed kidney disease only on the MR diet. Decreasing ERK signaling and methyl donors also caused demethylation and overexpression of the CD40lg gene in female mice, consistent with demethylation of the second X chromosome. Both the dietary methyl donor content and the duration of treatment influenced methylation and expression of the CD40lg gene. Conclusion: Dietary micronutrients that affect DNA methylation can exacerbate or ameliorate disease in this transgenic murine lupus model, and contribute to lupus susceptibility and severity through genetic–epigenetic interactions.